Microstructure evolution and mechanical properties of cold rolled Ti–Mo precipitation-hardened stainless steels after ageing treatment - Yu-Shan Chang; Chih-Yuan Chen (Journal of Materials Research and Technology)
While cold deformation prior to aging is a well-established approach for enhancing the mechanical properties of precipitation-hardened stainless steels (PHSSs), the synergistic effect of cold deformation and aging on microstructural evolution remains insufficiently explored. To investigate this effect, different levels (35 % and 70 %) of cold deformation strain (CDS) were applied, followed by aging at low (520 °C) and high (640 °C) temperatures, leading to variations in the formation of reverted austenite within the Ti–Mo PHSS. Regardless of the CDS, reverted austenite was observed only when aging was performed at 640 °C, while no significant austenite reversion occurred at 520 °C. Therefore, only aging was conducted at 640 °C, the trade-off relationship between strength and ductility improved with increasing CDS. This improvement was primarily due to the simultaneous formation of a higher density of η-Ni3Ti precipitates and reverted austenite during aging. These results indicate that optimizing metallurgical parameters can further enhance the mechanical performance of Ti–Mo PHSS, particularly by leveraging the effects of cold deformation strain and aging temperature on austenite reversion and precipitation behavior.